2022
DOI: 10.1055/a-1924-8268
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Endonasal Approach to the Craniovertebral Junction Lesions: A Case Series of 18 Patients

Abstract: Introduction: Odontoid pathologies constitute a special category because they may lead to instability. Instability is defined by abnormal spinal alignment under physiologic conditions (loads) such as standing, walking, bending, or lifting. Since instability poses a risk of cord damage, surgical interventions may be required for durable long-term stabilization. This study demonstrates operative technique and results of endoscopic endonasal approach to the odontoid. Methods: We conducted a retrospective study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…24 Other reported complications included pneumocephalus, hydrocephalus, and new neurologic deficits. 18,19,[25][26][27] Meta-analysis identified that neurologic complications occurred at a significantly higher rate in pediatric patients. One possible reason for this may be due to challenges in CSF leak closure in the clival and upper cervical spine region, which may be more difficult in children when reconstructive options such as the nasoseptal flap yield less surface area coverage, and therefore increasing their potential risk for postoperative CSF leak and meningitis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…24 Other reported complications included pneumocephalus, hydrocephalus, and new neurologic deficits. 18,19,[25][26][27] Meta-analysis identified that neurologic complications occurred at a significantly higher rate in pediatric patients. One possible reason for this may be due to challenges in CSF leak closure in the clival and upper cervical spine region, which may be more difficult in children when reconstructive options such as the nasoseptal flap yield less surface area coverage, and therefore increasing their potential risk for postoperative CSF leak and meningitis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%